IMPLEMENTASI KEBIJAKAN BEBAS VISA KUNJUNGAN - Masrul Ikhsan; Zaili Rusli; Febri Yuliani (JIANA ( Jurnal Ilmu Administrasi Negara ), 2018)
Policy Implementation of Visa Free Visits. This research is motivated by the implementation of Presidential Regulation Number 21 of 2016 on Visa Free Visits to 169 Countries in the Immigration Area of First Class Pekanbaru. The purpose of this study is to find out how the policy implementation of Visa Free visits  by Immigration Class I Pekanbaru in foreign supervision. This research uses qualitative approach with eskploratif research type. Key informants come from the Office of Immigration Class I Pekanbaru, Office of Manpower Riau Province, Municipal Labor Office Pekanbaru, Tourism Culture Office Pekanbaru, Kodim 0301 Pekanbaru, Pekanbaru Police and BNP Riau Province. Data collection techniques are interviews, observation and documentation. Data analysis uses interactive methods, ranging from data reduction, data presentation and conclusion. The results of this study indicate that Visa Free Visits Immigration Class I Pekanbaru not maximized, it is seen based on the element of inter-organizational relations behavior in the supervision of foreigners less coordinated so that it has inequality of authority between regional institutions and the behavior of lower level implementors who consider that the policy Visa-free visits will add to immigration work hours and harm the country. But related to the conductor in performing immigration traffic service at the Immigration Checkpoint of Sultan Syarif Kasim II Airport Pekanbaru to foreigners entering the city of Pekanbaru has done well.